A difícil relação com a língua estrangeira: um estudo de caso. - Coelho, Elisabeth Cavalcanti (2019)
In the contemporary world, many subjects seek outside their countries of origin for better professional and personal conditions. Thus, far from their mother tongue, they are faced with experiences of a new language and many face important difficulties because they cannot be captured by the foreign language, even residing abroad, a condition that could be a facilitator. Inquiries about this particularity culminated in the proposal of this Thesis, which aimed to investigate the relationship of a Brazilian resident abroad with the foreign language. The specific objectives were: to investigate to which refer the difficulties in relation with the foreign language; investigate the relationship with the mother tongue as a hindering aspect of foreign language capture. Therefore, it was theoretically based on the linguistic and psychoanalysis constructs, emphasizing, among others, the constitution of the unconscious subject, the capture by the mother tongue and the relationship with the foreign language, from reference authors in these areas of the subject. knowledge. From the methodological point of view, it was a qualitative research, configuring as a case study, a favorable method for the investigation of subjective realities. The research included Celina, a Brazilian who had lived abroad for over six years, as not captured by the foreign language. The instruments used were a questionnaire and semi-structured interviews, which took place via skype and whatsApp, recorded in audio and fully transcribed. From the transcription were selected clippings for analysis, considering speeches that indicated their position in front of the foreign language in everyday relationships. The results of the analysis of the interviews underscored the significant fear as the central core of his speech, which slid into other significant chains pointing directly or indirectly toward him. In this sense, we point to the idealized image of the speaker, which generates the effect of fear of making mistakes, making her silenced or unable to speak / feel speaking a foreign language and to her condition as an immigrant, placing her facing an inevitable departure from her mother tongue, a language that constitutes her as a subject of the unconscious. We highlight, then, effects of the mother tongue, the founding language on the relationship between this Brazilian and the foreign language, effects that indicated different difficulties in this relationship.